2013
DOI: 10.1002/pam.21705
|View full text |Cite
|
Sign up to set email alerts
|

Would a Value-Added System of Retention Improve the Distribution of Teacher Quality? A Simulation of Alternative Policies

Abstract: In this paper, we consider several features of teacher‐retention policies based on value‐added measures of effectiveness under a variety of empirically grounded rules and parameters. We consider the effects of policy design by varying the standard above which satisfactory teachers are expected to perform. We simulate recently adopted policies that remove teachers based on consecutive unsatisfactory performance and compare these to policies that remove teachers based on poor performance on average over a multiy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
0
39
1
1
Order By: Relevance
“…Perhaps the most important result for which consistent evidence has emerged in research is that students in K-12 schools stand to gain substantially from policies that incorporate information about value-added into personnel decisions for teachers (Boyd et al, 2011;Chetty, Friedman and Rockoff, 2014b;Condie, Lefgren and Sims, 2014;Dee and Wyckoff, 2013;Glazerman, 2013;Goldhaber, Cowan and Walch, 2013;Hanushek, 2009Hanushek, , 2011Rothstein, 2015;Winters and Cowen, 2013). The consistency of this result across the variety of policy applications that have been considered in the literature is striking.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Perhaps the most important result for which consistent evidence has emerged in research is that students in K-12 schools stand to gain substantially from policies that incorporate information about value-added into personnel decisions for teachers (Boyd et al, 2011;Chetty, Friedman and Rockoff, 2014b;Condie, Lefgren and Sims, 2014;Dee and Wyckoff, 2013;Glazerman, 2013;Goldhaber, Cowan and Walch, 2013;Hanushek, 2009Hanushek, , 2011Rothstein, 2015;Winters and Cowen, 2013). The consistency of this result across the variety of policy applications that have been considered in the literature is striking.…”
Section: Resultsmentioning
confidence: 90%
“…However, on the other hand, any decisions based on VAM estimates will be less than perfectly correlated with the decisions one would make if valueadded was known with certainty, and it is theoretically unclear whether using imperfect data in teaching is less beneficial (or more costly) than in other professions. The most compelling evidence on this question comes from studies that, taking the instability into account, evaluate the merits of acting on estimates of teacher value-added to improve workforce quality (Chetty, Friedman and Rockoff, 2014b;Boyd et al, 2011, Goldhaber andWinters and Cowen, 2013;Rothstein, 2015). These studies consistently show that using information about teacher value-added improves student achievement relative to the alternative of not using value-added information.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional considerations for policy design include the nature of the teacher labor market and the role of natural attrition of teachers. Simulation modeling by Winters and Cowen (2013) demonstrates that effects of dismissal policies based on value-added could be substantially influenced by the size and nature of the labor market, such that in limited labor markets, the potential for positive effects of dismissal policies could be markedly reduced. Also, Winters and Cowen (2013) found that when natural attrition of teaches is incorporated into simulation modeling, the potential for positive effects of dismissal policies are reduced, due to the fact that less effective teachers are more likely to leave the profession.…”
Section: Policy Design Considerationsmentioning
confidence: 99%
“…Simulation modeling by Winters and Cowen (2013) demonstrates that effects of dismissal policies based on value-added could be substantially influenced by the size and nature of the labor market, such that in limited labor markets, the potential for positive effects of dismissal policies could be markedly reduced. Also, Winters and Cowen (2013) found that when natural attrition of teaches is incorporated into simulation modeling, the potential for positive effects of dismissal policies are reduced, due to the fact that less effective teachers are more likely to leave the profession. Cowen and Winters (2015) conclude that "the quality and number of teachers dismissed under value-added policies depends heavily on policy design" (p. 331).…”
Section: Policy Design Considerationsmentioning
confidence: 99%